Prevalence of Anxiety Symptoms and Associated Clinical and Sociodemographic Factors in Mexican Adults Seeking Psychological Support for Grief During the COVID-19 Pandemic: A Cross-Sectional Study - Dominguez-Rodriguez, Alejandro; Herdoiza-Arroyo, Paulina Erika; Martínez Arriaga, Reyna Jazmin; Bautista Valerio, Eduardo; Mateu Mollá, Joaquín; de la Rosa-Gómez, Anabel; Farfallini, Luis; Hernández Jiménez, María Jesús; Esquivel Santoveña, Esteban Eugenio; Ramírez-Martínez, Flor Rocío; Castellanos Vargas, Rosa Olimpia; Arzola-Sánchez, Carlos Armando; et al. (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic is one of the greatest challenges in modern history, with more than four million confirmed deaths worldwide. To date, evidence regarding the psychological impact of the COVID-19 pandemic on grievers is scarce for developing countries such as Mexico. This study aimed to assess the levels of anxiety and associated concerns in a sample of Mexican adults bereaved during the COVID-19 outbreak. A cross-sectional study was conducted through the Duelo COVID (COVID Grief) platform, which is a self-guided online treatment. A total of 5,224 participants reported their anxiety, depression, sleep quality, avoidance, and arousal, prolonged grief symptoms and medication consumption. Independent sample Mann-Whitney U tests, chi-square tests, and Kruskal-Wallis tests, as well as multinomial logistic regression, were conducted. Results indicated that 90.4% of the participants reported clinical levels of anxiety, depression, and sleep affectations. The people who lost someone during the last five months scored higher in normal grief symptoms compared to the people whose loss was six months ago or more, 9.8% of individuals reported the use of prescription medication, with anxiolytics and antidepressants being the most common. Females, younger respondents, unemployed people with a lower educational level, and participants who disclosed a recent suicide attempt were among those who reported medication consumption. Sleep problems were more frequent in older participants.